New Women: trans women, hijras, and the remaking of inequality in India - Mount, Liz (UK Cambridge University Press, 2024)
Recent global attention to transgender issues and new opportunities for trans people can appear as positive and progressive social change. 'New' Women challenges this assumption through an ethnography of emerging trans women and traditional gender non-conforming hijras in India. In many countries, people identify as either cisgender or non-cis identities like transgender and nonbinary. India is unique for its recognized, yet stigmatized, gender non-conforming hijras. This book explores changes in hijra groups due to economic liberalization and LGBTQ+ advocacy, particularly the rise of the trans woman. Liz Mount locates trans women within patriarchal and postcolonial histories that shape ideal womanhood in India. As trans women align themselves with middle-class, respectable (cisgender) womanhood, they distance themselves from hijras, perpetuating their exclusion. Ultimately, this intersectional feminist analysis shows that new forms of gender identity can reinforce old inequalities and what appears as progressive change for some trans people can marginalize others.
Keywords: Gender, and sexuality studies; Asian Studies; Sociology